The effect of past earnings and dividend patterns on the information content of dividends when earnings are reduced - Theodoulou, Giorgos; Lambertides, Neophytos; Charitou, Andreas (My University, 2010)
This study pursues two objectives: first, to provide evidence on the information content of dividend policy, conditional on past earnings and dividend patterns prior to an annual earnings decline; second, to examine the effect of the magnitude of low earnings realizations on dividend policy when firms have more-or-less established dividend payouts. The information content of dividend policy for firms that incur earnings reductions following long patterns of positive earnings and dividends has been examined (DeAngelo et al., 1992, 1996; Charitou, 2000). No research has examined the association between the informativeness of dividend policy changes in the event of an earnings drop, relative to varying patterns of past earnings and dividends. Our dataset consists of 4,873 U.S. firm-year observations over the period 1986-2005. Our evidence supports the hypotheses that, among earnings-reducing or loss firms, longer patterns of past earnings and dividends: (a) strengthen the information conveyed by dividends regarding future earnings, and (b) enhance the role of the magnitude of low earnings realizations in explaining dividend policy decisions, in that earnings hold more information content that explains the likelihood of dividend cuts the longer the past earnings and dividend patterns. Both results stem from the stylized facts that managers aim to maintain consistency with respect to historic payout policy, being reluctant to proceed with dividend reductions, and that this reluctance is higher the more established is the historic payout policy. © 2010 The Authors. Journal compilation
Keywords: Dividend omissions; Dividend reductions; Dividend-payment patterns; Dividends; Earnings patterns; Earnings reductions; Information content; Losses